2023
DOI: 10.3389/fnagi.2023.1206123
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's early detection in post-acute COVID-19 syndrome: a systematic review and expert consensus on preclinical assessments

Clair Vandersteen,
Alexandra Plonka,
Valeria Manera
et al.

Abstract: IntroductionThe risk of developing Alzheimer's disease (AD) in older adults increasingly is being discussed in the literature on Post-Acute COVID-19 Syndrome (PACS). Remote digital Assessments for Preclinical AD (RAPAs) are becoming more important in screening for early AD, and should always be available for PACS patients, especially for patients at risk of AD. This systematic review examines the potential for using RAPA to identify impairments in PACS patients, scrutinizes the supporting evidence, and describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
(220 reference statements)
0
0
0
Order By: Relevance
“…Clinical follow-up studies with the intent of evaluating the extent and the duration of cognitive impairment in large cohorts of COVID-19 patients along with further experimental investigations on SARS-CoV-2-infected human brain organoids possibly recapitulating the phenotypic expression of key AD hallmarks are still needed. From a translational point of view, the concerted effort from clinicians, researchers, patients, caregivers and health and social care agencies, in association with a deep understanding of the biological aspects linking COVD-19 and AD physiopathologies, will help in designing specific diagnostic/therapeutic strategies [274,275], in order to mitigate the impact of long-lasting neurological and ophthalmological COVID-19 complications in the aging population.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Clinical follow-up studies with the intent of evaluating the extent and the duration of cognitive impairment in large cohorts of COVID-19 patients along with further experimental investigations on SARS-CoV-2-infected human brain organoids possibly recapitulating the phenotypic expression of key AD hallmarks are still needed. From a translational point of view, the concerted effort from clinicians, researchers, patients, caregivers and health and social care agencies, in association with a deep understanding of the biological aspects linking COVD-19 and AD physiopathologies, will help in designing specific diagnostic/therapeutic strategies [274,275], in order to mitigate the impact of long-lasting neurological and ophthalmological COVID-19 complications in the aging population.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Available RDA include digital tasks and games, voice recording, video and motor sensors, olfactory screenings, as well as hearing and vision screenings [2]. During the CO-VID-19 pandemic, RDA became increasingly used in daily clinical practice, and evidence rapidly accumulated on their feasibility, acceptability, and efficacy [3,4]. For instance, a recent review showed that digital cognitive biomarkers achieved comparable or even better diagnostic performance than traditional paper-and-pencil tests [5].…”
Section: Introductionmentioning
confidence: 99%